Analisis Pelaksanaan Kinerja Pegawai Pada Kantor Di PT XYZ - Muhammad Dzaky Pradana; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to the research. The purpose of this research is to determine the analysis of the implementation of employee performance in the office at PT XYZ which includes maintenance scheduling as well as obstacles and solutions in analyzing the implementation of employee performance in the office. From the results of this research, it can be seen that the implementation of employee performance at the PT XYZ office has performed well.